Barley Brassinosteroid Mutants Provide an Insight into Phytohormonal Homeostasis in Plant Reaction to Drought Stress - Gruszka, Damian; Janeczko, Anna; Dziurka, Michal; Pociecha, Ewa; Oklestkova, Jana; Szarejko, Iwona (Frontiers in Plant Science, 2016)
Brassinosteroids (BRs) are a class of steroid phytohormones, which regulate various processes of morphogenesis and physiology – from seed development to regulation of flowering and senescence. An accumulating body of evidence indicates that BRs take part in regulation of physiological reactions to various stress conditions, including drought. Many of the physiological functions of BRs are regulated by a complicated, and not fully elucidated network of interactions with metabolic pathways of other phytohormones. Therefore, the aim of this study was to characterize phytohormonal homeostasis in barley (Hordeum vulgare) in reaction to drought and validate role of BRs in regulation of this process. Material of this study included the barley cultivar ‘Bowman’ and five Near-Isogenic Lines (NILs) representing characterized semi-dwarf mutants of several genes encoding enzymes participating in BR biosynthesis and signaling. Analysis of endogenous BRs concentrations in these NILs confirmed that their phenotypes result from abnormalities in BR metabolism. In general, concentrations of eighteen compounds, representing various classes of phytohormones, including brassinosteroids, auxins, cytokinins, gibberellins, abscisic acid, salicylic acid and jasmonic acid were analyzed under control and drought conditions in the ‘Bowman’ cultivar and the BR-deficient NILs. Drought induced a significant increase in accumulation of the biologically active form of BRs – castasterone in all analyzed genotypes. Another biologically active form of BRs – 24-epi-brassinolide - was identified in one, BR-insensitive NIL under normal condition, but its accumulation was drought-induced in all analyzed genotypes. Analysis of concentration profiles of several compounds representing gibberellins allowed an insight into the BR-dependent regulation of gibberellin biosynthesis. The concentration of the gibberellic acid GA7 was significantly lower in all NILs when compared with the ‘Bowman’ cultivar, indicating that GA7 biosynthesis represents an enzymatic step at which the stimulating effect of BRs on gibberellin biosynthesis occurs. Moreover, the accumulation of GA7 is significantly induced by drought in all the genotypes. Biosynthesis of jasmonic acid is also a BR-dependent process, as all the NILs accumulated much lower concentrations of this hormone when compared with the ‘Bowman’ cultivar under normal condition, however the accumulation of jasmonic acid, abscisic acid and salicylic acid were significantly stimulated by drought.